(untitled) (Journal of the College of Basic Education, 2022)
The art of design is one of the first arts that expressed the human need, as it is a dialogue between the designer and the consumer, as it requires awareness and creative and artistic capabilities that influence the design work. Fabrics have a wide space in this world, which made the interest in these designs increase day by day in line with the consumer’s desire. The method, material, and display technique that is relied upon to show the final product of the upholstery fabric design, and accordingly the researcher created a justification to study the current research topic tagged with pictorial formations and the possibility of employing them in the designs of upholstery fabrics, where the research included three chapters. for graphic formations in upholstery fabric designs)? In order to shed light on the graphic formations in the design of upholstery fabrics and to enhance the cognitive frameworks in the design of fabrics, and thus the research objectives came: 1- To reveal the graphic formations in the designs of printed upholstery fabrics. The study by employing pictorial formations in the designs of printed upholstery fabrics used in home furniture - sofas, available in the local markets of the city of Baghdad with origin (Turkish_Chinese) from the year 2021-2022 or the second chapter included the theoretical framework, which included first: The concept of the image in the design and includes 1- The role of pictorial composition in the design of fabrics 2- The function and its role in the designs of upholstery fabrics.. Second: Characteristics and specifications of upholstery fabrics and third: printing techniques for designs of upholstery fabrics. Then the most important indicators that resulted from the theoretical framework were extracted. As for the third chapter, it dealt with the research procedures, which included the research methodology, the analytical description, and the research community (30) design models after excluding repeated and unclear models. (3) A design model, and it also included the presentation of the research results, which are: 1- The image has an important role in that it organizes the collection of parts of images included in the design construction and contributes to the creation of the general form in which aesthetic and functional values ​​​​of the design work appear. The design and the use of the image as a formal unit, that is, the unity was achieved based on the image for the structure of the multiple elements in the design form, as the diversity appeared in the formal containment. As for the conclusions, they included 1- The designs of the upholstery fabrics depended on the mixed industrial material (polyester and cotton) due to its quality, softness and comfort during use, as well as its features and characteristics in showing the aesthetic aspects. 2- The models showed the effectiveness of the visual units depicted through the representation of the graphic scene of the formal composition in the designs of fabrics and its technical and visual design diversity. Through the recommendations, the researcher stressed the need to pay attention to modern printing techniques that interact with the design units to produce them in their integrated form for the designs of upholstery fabrics. And then submit a design proposal, a list of sources and a summary of the research in English.